Na‐Induced Conversion of a Notorious Fine‐Grained Residue Layer into a Working Absorber in Solution‐Processed CuInSe2 Devices. Issue 11 (15th August 2019) - Moon, Jihyun; Rehan, Shanza; Rana, Tanka Raj; O, Byungsung; Ahn, Seung Kyu; Ahn, SeJin
Abstract : Na has been reported to increase the efficiency of not only vacuum‐processed but also the solution‐processed Cu(In, Ga)(Se, S)2 (CIGSSe)‐type solar cells. However, the physical mechanism underlying the improvement is significantly different depending on the nature of the processes, as exemplified by the experimental observation that the short circuit current density ( J SC ) of the solution‐processed devices reportedly increases upon Na addition, whereas that of the vacuum‐processed devices remains the same or even decreases. A systematic study is conducted to elucidate the reason for this Na‐induced J SC increase in the solution‐processed CuInSe2 (CISe) devices. In the amorphous nanoparticle‐based route, upon Na addition, the previously fine‐grained bottom layer near the CISe/Mo interface is transformed into a large‐grained layer, presumably because of the Na–Se liquid flux‐assisted sintering. At the same time, Na also induces phase homogenization in the bottom layer in which the mixed‐phases are converted to single‐phase CISe upon Na addition. These morphological and phase transformations are found to be directly related to the improved collection of the minority carriers generated in this region, which suggests to be the main reason for the observed J SC increase. Abstract : The notorious fine‐grained bottom layer in solution‐processed CuInSe2 thin films is converted into a working absorber upon Na addition, leading to a significant increase in the collection length and finally short current density of the devices.